Development versus predation: Transcriptomic changes during the lifecycle of Myxococcus xanthus - Pérez, Juana; Contreras-Moreno, Francisco Javier; Muñoz-Dorado, José; Moraleda-Muñoz, Aurelio (Frontiers in Microbiology, 2022)
Myxococcus xanthus is a multicellular bacterium with a complex lifecycle. It is a soil-dwelling predator that preys on a wide variety of microorganisms by using a group and collaborative epibiotic strategy. In the absence of nutrients this myxobacterium enters in a unique developmental program by using sophisticated and complex regulatory systems where more than 1400 genes are transcriptional regulated to guide the community to aggregate into macroscopic fruiting bodies filled of environmentally resistant myxospores. Herein, we analyze the predatosome of M. xanthus, that is, the transcriptomic changes that the predator undergoes when encounters a prey. This study has been carried out using as a prey Sinorhizobium meliloti, a nitrogen fixing bacteria very important for the fertility of soils. The transcriptional changes include upregulation of genes that help the cells to detect, kill, lyse, and consume the prey, but also downregulation of genes not required for the predatory process. Our results have shown that, as expected, many genes encoding hydrolytic enzymes and enzymes involved in biosynthesis of secondary metabolites increase their expression levels. Moreover, it has been found that the predator modifies its lipid composition and overproduces siderophores to take up iron. Comparison with developmental transcriptome reveals that M. xanthus downregulates the expression of a significant number of genes coding for regulatory elements, many of which have been demonstrated to be key elements during development. This study shows for the first time a global view of the M. xanthus lifecycle from a transcriptome perspective.